Pengembangan Aplikasi Penentu Kadar Hidrokuinon berbasis Android (Studi Kasus: Laboratorium Kimia Analitik Fakultas MIPA UB) - Nyoman Putra Utama; Adam Hendra Brata; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Analytical Chemistry Laboratory is one of the seven laboratories in the Chemistry Department. One of the activities in analytical chemistry laboratory is to test the level of hydroquinone solution. Hydroquinone is a compound that is toxic when inhaled by the nose and in direct contact with eyes and skin. Hydroquinone analysis using spectrophotometry method is one method that is fast compared to other methods but in determining the level of hydroquinone solution using the UV spectrophotometry method must understand the use of UV spectrophotometer so it requires time to learn the use of the instrument. In using a UV spectrophotometer the device must wait for 30 minutes after the device is turned on to perform a calibration so that it can be used in conducting analysis. In this research, the authors developed an application based on Android-based levels of hydroquinone solution to assist in analyzing the levels of hydroquinone solutions using RGB color codes from smartphone camera photo results which were then performed calculations using lambert-beer law in determining the levels of hydroquinone solutions. The application is built using the prototyping method because the requirements of the system have not been fully defined at the beginning. The results of functional tests which include unit testing, integration, and validation obtained 100% valid results. The results of non-functional testing are compatibility testing with system results that can be run on the Android operating system with a minimum version of 7.0 to 10.0.